Four days a week or less on appropriate anti‐HIV drug combinations provided long‐term optimal maintenance in 94 patients: the ICCARRE project. Issue 6 (1st April 2015) - Leibowitch, Jacques; Mathez, Dominique; de Truchis, Pierre; Ledu, Damien; Melchior, Jean Claude; Carcelain, Guislaine; Izopet, Jacques; Perronne, Christian; David, John R.
ABSTRACT: Short, intraweekly cycles of anti‐HIV combinations have provided intermittent, effective therapy (on 48 patients) (1). The concept is now extended to 94 patients on treatment, 4 days per week or less, over a median of 2.7 discontinuous treatment years per patient. On suppressive combinations, 94 patients volunteered to treatment, 5 and 4 days per week, or reduced stepwise to 4, 3, 2, and 1 days per week in 94, 84, 66, and 12 patients, respectively, on various triple, standard, antiviral combinations, or nonregistered, quadruple, antiviral combinations. Ninety‐four patients on treatment 4 days per week aggregated 165 intermittent treatment years; no viral breakthrough was observed over 87 average treatment weeks per patient, 63 of 94 having passed 2.5 intermittent treatment years on any of the antiviral combinations prescribed. On the hyperintermittent treatment of 3, 2, and 1 days per week, HIV RNA surged >50 copies, 4 weeks apart, in 18 instances (6.8 viral escapes/100 hyperdiscontinuous maintenance years). Viral escapes could have been a result of erratic adherence (EA) to regimen or follow‐up (3 patients)—drug taken at half of the daily recommended dosage (8 patients) and/or overlooked archival‐resistant HIVs from antecedent treatment failures (6 patients). Aside from the above circumstances, HIV unexpectedly rebounded in 3 patients on 2 days per week treatment and 1 patient on 1 day per week treatment, posting 2.2 intrinsic viral escapes/100 highly discontinuous treatment years. All 18 escapes were eventually reversed by 7 days per week salvage combinations, and 11 of 18 patients have been back for a second course of intermittent therapy, 4 days per week or less. Both cell‐activation markers on the surface of T lymphocytes and cell‐bound HIV DNA levels remained stable or declined. CD4/CD8 ratios rose to ≤1 in 35% of patients, whereas CD4 counts went ≤500/μl in 75%. These values were previously 7 and 40%, respectively, on 7 days per week therapy. In our aging, long, HIV‐enduring, multitreated patient cohort, treatment 4 days per week and less over 421 intermittent treatment years reduced prescription medicines by 60%—equivalent to 3 drug‐free/3 virus‐free remission year per patient—actually sparing €3 million on just 94 patients at the cost of 2.2 intrinsic viral failure/100 hyperintermittent treatment years. At no risk of viral escape, maintenance therapy, 4 days per week, would quasiuniversally offer 40% cuts off of current overprescriptions.—Leibowitch, J., Mathez, D., de Truchis, P., Ledu, D., Melchior, J. C., Carcelain, G., Izopet, J., Perronne, C., David, J. R. Four days a week or less on appropriate anti‐HIV drug combinations provided long‐term optimal maintenance in 94 patients: the ICCARRE project. FASEB J. 29, 2223‐2234 (2015). www.fasebj.org